2009
DOI: 10.1063/1.3081025
|View full text |Cite
|
Sign up to set email alerts
|

Point defects in sputtered NiO films

Abstract: The dominant point defects in p-type NiO films were determined by analyzing the coordination number (CN) change with various annealing temperatures and the composition profile of double-layer films deposited individually in oxygen and in argon atmospheres. The results show that the nonstoichiometry of sputtered NiO film is determined by the number of nickel atoms rather than by the number of oxygen atoms. It is concluded that nickel vacancies are the dominant point defects that result in the electrical conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
69
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(75 citation statements)
references
References 10 publications
6
69
0
Order By: Relevance
“…Such relaxation of atomic structure, induced by the presence of nickel vacancy, plays significant role in the average structure relaxation, especially for the first coordination shell of nickel, as was found recently. 42 The results of our simulations are in excellent agreement with those from the recent ab initio calculations 65,66 of the structure relaxation around Ni vacancy, which predict the relaxation of O atoms by about 0.17Å outwards from the vacancy. This fact confirms the ability of our simple force-field potential model to reproduce well structure relaxation around nickel vacancies.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Such relaxation of atomic structure, induced by the presence of nickel vacancy, plays significant role in the average structure relaxation, especially for the first coordination shell of nickel, as was found recently. 42 The results of our simulations are in excellent agreement with those from the recent ab initio calculations 65,66 of the structure relaxation around Ni vacancy, which predict the relaxation of O atoms by about 0.17Å outwards from the vacancy. This fact confirms the ability of our simple force-field potential model to reproduce well structure relaxation around nickel vacancies.…”
Section: Resultssupporting
confidence: 80%
“…It was concluded that nickel vacancies, being the dominant point defects, are responsible for the electrical conductivity of the films 42 and for the film decomposition under annealing in vacuum above 400…”
Section: 43mentioning
confidence: 99%
“…As for the point defect structure of NiO, it has been investigated earlier with different experimental techniques including thermogravimetry, 47 electrical conductivity, 48,49 and perturbed angular correlation spectroscopy. 50 Thus, there is a general agreement that the primary point defects in NiO are metal vacancies.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, our positron annihilation results are consistent with previous experimental results. [47][48][49][50][51] Fig . 5 shows τ 1 , τ 2 and the corresponding intensities (I 1 , I 2 ) in the NiO nanocrystals annealed at different temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation